Proses Gatekeeping Berita Citizen Journalism Pada Akun Instagram @prfmnews - Nur Yusuf, Dema Rahmi; Suryana, Cecep; Dulwahab, Encep (Annaba: Jurnal Ilmu Jurnalistik, 2024)
In today's digital era, Citizen Journalism has become a significant phenomenon, where the general public actively participates in collecting, reporting, and disseminating news. The Instagram account @prfmnews utilizes Citizen Journalism to deliver news to its audience. This research aims to understand the gatekeeping process carried out by @prfmnews in publishing Citizen journalism-based news, the role of Gatekeeper s in news production, and the forms of Citizen Journalism news on the @prfmnews Instagram account. This study employs a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation. The results indicate that the gatekeeping process at @prfmnews involves selecting and verifying information from the public before publication. Gatekeeper s at @prfmnews play a crucial role in ensuring that the content published is accurate and adheres to journalistic standards, avoiding the spread of false information or hoaxes. Citizen Journalism news on @prfmnews reflects a diversity of perspectives and a close connection to the local community.